Cross contamination of Listeria monocytogenes in ready-to-eat meat product during slicing: a predictive approach - Lopes, Janaina Thaís (2017)
Ready to eat (RTE) meat products are subject to recontamination after industrial processing, mainly by Listeria monocytogenes, a pathogenic microorganism that can persist for a long time in the environment. A RTE meat product that is contaminated with L. monocytogenes due to cross contamination during some stage after industrial processing, such as weighing, slicing or wrapping, can be an important causer of disease, due to absence of a kill step before consumption. The objective of this project was to measure the transfer of L. monocytogenes during slicing of cooked ham (cross contamination) at retail, simulating in the laboratory the practices in commercial slicing, and to develop a predictive model capable of describing this transfer. It was observed that in the first slices obtained after the experimental contamination of the slicer, the counts and the transfer rates of L. monocytogenes were higher than in the subsequent slices, and the counting curves presented a long tail as the slices were obtained. The data demonstrate that the slicer may be a relevant source of cross contamination of L. monocytogenes for RTE meat products, regardless of the level of contamination of the slicer. With the data obtained, a new transfer model was proposed called 4p-2se, as it contained four parameters (4p) and two environments (2se), and was independent of the quantification of the pathogen transferred to the slicer. The proposed model was compared to two pathogen transfer models previously described, and the predicted data presented lower RMSE (Root Mean Sum of squared errors) values than the other models. The 4p-2se model was able to satisfactorily predict the pathogen transfer data during slicing of cooked ham, which could assist the food retail establishments and regulatory agencies in the evaluation and control of cross contamination of RTE foods and in the design of proper risk management strategies.